Systematics of Student Misconceptions on the Topics of Gravity and Potential Energy: A Systematic Literature Review - Rizky Nurul Muslih; Caroline Glorya Manurung; Dzikri Anjar Susilo Sasongko; Afridha Laily Alindra (BIOCHEPHY: Journal of Science Education, 2026)
Understanding of basic science concepts is often hindered by students' misconceptions regarding phenomena in their surroundings. If left unaddressed, these misconceptions will obscure and interfere with students' future comprehension of more complex physics material. This study aims to identify the patterns of misconceptions among elementary school students on the topics of gravity and potential energy, evaluate the effectiveness of the diagnostic instruments used, and identify the contributing factors. Employing a descriptive qualitative approach, this systematic literature review analyses various scientific sources published between 2022 and 2026. The findings reveal consistent conceptual errors, particularly the assumption that mass affects the falling speed of an object and the belief that potential energy exists only in moving objects. The primary triggering factors include students' personal intuition, conventional teaching methods, and limitations in visual media. In conclusion, the regular implementation of tiered diagnostic instruments, accompanied by a shift toward technology-based learning models, is essential for overcoming these learning obstacles.